Malignancies in HIV-infected children at Siriraj Hospital - Kleebsabai Sanpakit (2018)
Background: Some malignancies such as Kaposi's sarcoma, non-Hodgkin's lymphoma (NHL) are one of the acquired immunodeficiency syndrome (AIDS) - defining illnesses. With the improving survival of patients with AIDS due to better prevention and treatment of infectious complications, there may well be an increase in AIDS-related malignancies. Objective: To study malignancies in human immunodeficiency virus (HIV)-infected children in view of demographic data, HIV disease status, characters of malignancies, and treatment outcome. Method: Retrospective study was performed in HIV-infected children with malignancies at Siriraj Hospital from January 1995 to October 2001. Results: During the 6 year and 10 month period, there were 7 HIV-infected children (2 boys, 5 girls) with malignancies. Mean age at diagnosis of malignancies was 3 years 7 months (2 years 6 months - 5 years). Hepatomegaly and lymphadenopathy were the most common presenting symptoms. All patients had NHL stage III or IV. Burkitt's lymphoma was the predominant type. Six patients were treated with appropriate chemotherapy and one patient also received antiretroviral therapy. Only one patient with large cell lymphoma stage IV who received both antiretroviral and chemotherapy has survived to date. Five patients died during chemotherapy treatment and one patient died before receiving chemotherapy. Causes of death of these patients were infections. One of them with Burkitt's lymphoma stage III also had central nervous system (CNS) relapse at the time of death. Mean survival time after diagnosis with malignancies was 11 months (15 days - 3 years 1 month). Conclusion: NHL is the most common malignancy in HIV-infected children at Siriraj Hospital. Age at presentation of NHL in these children is younger than their non-HIV counterpart. Outcome of treatment is poor. Adjustment protocol for treatment of malignancy in HIV-infected children combined with antiretroviral therapy for controlling HIV infection should be studied further.